Utilization of a Mixture of Peuyeumization Market Waste-Derived RDF (Refuse-Derived Fuel) and Coconut Shell Charcoal (CSC) into Bio-Briquettes with Coal-Calorific Value - Elfiana, Elfiana; Intan, Syarifah Keumala; Ruhana, Ruhana; Rahmahwati, Cut Aja; Zaini, Halim (Jurnal Teknologi, 2025)
The accumulation of market waste and coconut shells poses a significant environmental challenge, necessitating effective management strategies by both local governments and academic institutions. This study explores the conversion of organic market waste into Refuse-Derived Fuel (RDF) through a dry fermentation (peuyeumization) process using 5% EM4 bio-activator over a 21-day incubation period. Concurrently, coconut shells were carbonized to produce high-carbon Coconut Shell Charcoal (CSC). Both RDF and CSC, ground to a 100-mesh particle size, were utilized to produce cylindrical bio-briquettes (7 cm height, 3.6 cm outer diameter, 1.6 cm inner diameter) using a compaction method. Various RDF:CSC ratios (0:100, 25:75, 50:50, 75:25, and 100:0) were tested with three concentrations of tapioca starch adhesive (6%, 8%, and 10%). The quality of the resulting briquettes was evaluated based on the Indonesian National Standard (SNI 01-6235-2000), assessing parameters such as moisture content, ash content, density, fixed carbon content, and calorific value. Combustion characteristics were further examined through ignition time and combustion rate measurements. The optimal briquette was produced at a 25:75 RDF:CSC ratio with 6% adhesive, achieving a weight of 30 g, density of 0.46 g/mL, fixed carbon content of 75.51%, moisture content of 5.25%, ash content of 5.91%, calorific value of 6117.38 cal/g, ignition time of 63.78 minutes, and combustion rate of 1.55 g/min. These findings indicate that the bio-briquettes meet the calorific standard of young coal, supporting their potential use as an environmentally friendly alternative fuel.